Coumarin derivative trigger controlled photo-healing of ion gels and photo-controlled reversible adhesiveness. (5th February 2021) - Wang, Lei; Ma, Xiaofeng; Wu, Linlin; Sha, Ye; Yu, Bo; Lan, Xiaoyu; Luo, Yanlong; Shi, Yijun; Wang, Yan; Luo, Zhenyang
Graphical abstract: Highlights: Coumarin containing random copolymers (P(DMA- r -MAOEMC)) are prepared. Photodimerization and photocleavage behavior of coumarin group in P(DMA- r -MAOEMC) are reversible. P(DMA- r -MAOEMC) in ionic liquid (ion gel) show photo-induced reversible sol–gel transition. Ion gel shows photo-healing property and photo-induced reversible adhesiveness. Abstract: Fabrication strategies for photo-responsive ion gels have attracted attention owing to their precise spatial and temporal control with predetermined responses to light stimuli. In this work, a reversible light-driven method was introduced to devise photo-responsive ion gels by harnessing coumarin-based building blocks under 365 nm irradiation. A series of random copolymers composed of N, N -dimethylacrylamide (DMA) and 7-(2′-methacryloyloxyethoxy)–4-methylcoumarin (MAOEMC), namely P(DMA- r -MAOEMC), were synthesized through reversible addition-fragmentation chain transfer (RAFT) polymerization with sufficient molecular weight (≈100 kDa). The coumarin moieties in those polymers exhibited a reversible photo-induced dimerization and photocleavage behavior in 1-ethyl-3-methylimidazolium bis (trifluoromethylsufonyl) imide ([C2 mim][NTf2 ]). Those polymers - ionic liquid system at high polymer concentration (20 wt%) under suitable wavelength UV light irradiation led to sol–gel transition, which could be functionalized as photo-healable material and photo-controlled adhesion agents. Notably, the photo-controlled adhesiveness was reversible and can be mediated from 1.2 MPa to 0.2 MPa. This work opens new avenues to develop multifunctional ion gels using dynamic covalent bonds.